DAYA TERIMA DAN ANALISIS ZAT GIZI MAKRO PADA PEMBUATAN MISUKE (MINYAK SUSU KEDELAI) - Hikmawati Mas'ud; Musdalipah Musdalipah (Jurusan Gizi Poltekkes Kemenkes Makassar, 2020)
ABSTRACT Misuke is solid food consisting of vegetable oil, skim milk, and soy which is a source of energy and high protein but with a small volume and in the form of powder. Soybean is a food ingredient with complete protein and is one of the food ingredients that contain amino acids needed by the body. This study is to determine the acceptability of Misuke (soybean oil) and the analysis of macronutrient content (protein, fat, and fat). This research is pre-experimental research that is making Misuke (soybean oil) using three variations of vegetable oil composition (8 ml, 10 ml, and 12 ml), and collecting resources based on color, aroma, texture, and taste. Data analysis using the Friedman Test in a computerized program. The results showed the panelist's most interesting formula on aspects of color, aroma, texture, and taste of Misuke (soybean oil) with an 8 ml vegetable oil composition. In 1 portion of Misuke (soy milk oil), a protein with 8 ml, 10 ml and 12 ml vegetable oil composition is 5.7 g, 5.4 g, 5.3 g while the fat content with vegetable composition is 8 ml, 10 ml and 12 ml, namely 8.1 g, 8.2 g, 8.5 g and fat composition with vegetable oil composition 8 ml, 10 ml and 12 ml, 4.9 g, 5.0 g, 4.2 g. Only for children, children must pay for their children. Keywords: Acceptability, Misuke (Soymilk Oil)